The Existence of Water Transportation Facilities and Infrastructure in Tourism Industry - Agus Darmawan; Umi Dian Adhitya Wulan Ningrum; Febrianti Febrianti (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
There are many tourism objects in Anambas Islands Regency, namely in the form of beach tourism, nature tourism, underwater tourism, historical tourism, as well as cultural and educational tourism, but their utilization is not optimal. The main obstacle faced is the limited condition of facilities and infrastructure both to go to tourist objects and to locations of tourist objects, and the low capacity of community resources in tourism activities. If the tourism sector develops, it will certainly encourage overall regional economic growth, therefore the tourism potential of this area needs to be maximally utilized, so that it becomes one of the backbone of the economic development of the Anambas Islands region. Meanwhile, one of the supporting factors for tourism activities that need to be developed is sea transportation facilities for tourist transportation which are not yet available. This research begins with the identification of problems through secondary data followed by field observations and then evaluated. From the results of the analysis, it can be concluded that for the suitable facilities to be developed is the Catamaran type fast boat, while for land transportation infrastructure it needs to be improved, especially those that go to tourist objects. In addition, transportation nodes at seaports need to be developed, including tourism information centers and the active involvement of local.